Morphological Stylistic Analysis in William Blake’s Poem “Spring” - Nasution, Atikah Auni; Matanari, Desna Uli; Fianda, Afiqah; Sasmita, Rheina; Rangkuti, Rahmadsyah (English Language and Literature, 2024)
Morphemes used in the poem can alter the reader's perception and interpretation of the poem's meaning and message. It demonstrates the variety of language and the freedom of expression enabled by using morphemes in literature, particularly poems. This study aims to identify several types of free and bound morphemes, such as lexical, functional, derivational, and inflectional morphemes found in William Blake's Poem "Spring." The researchers analyzed the data using a descriptive-qualitative method. Based on this research, William Blake's Poem "Spring" has 27 lines. This research showed William Blake's poem "Spring" contained 83 morphemes. Lexical morpheme was the most frequently found (56%). The second most common was functional morpheme (31%), derivational morpheme (8%), and the least inflectional morpheme (5%). Therefore, a number of morphemes in William Blake's poem "Spring" were dominated by lexical morphemes. This poem emphasizes the poet's desire to explore ideas through the use of a variety of words and phrases.